Loop Between NLRP3 Inflammasome and Reactive Oxygen Species - Dominic, Abishai; Le, Nhat-Tu; Takahashi, Masafumi (Antioxidants & redox signaling, 2022)
Inflammasomes are cytosolic multiprotein complexes that mediate innate immune pathways. Inflammasomes activate inflammatory caspases and regulate inflammatory cytokines interleukin (IL)-1β and IL-18 as well as inflammatory cell death (pyroptosis). Among known inflammasomes, NLRP3 (NLR family pyrin domain containing 3) inflammasome is unique and well studied owing to the fact that it senses a broad range of stimuli and is implicated in the pathogenesis of both microbial and sterile inflammatory diseases. Reactive oxygen species (ROS), especially derived from the mitochondria, are one of the critical mediators of NLRP3 inflammasome activation. Furthermore, NLRP3 inflammasome-driven inflammation recruits inflammatory cells, including macrophages and neutrophils, which in turn cause ROS production, suggesting a feedback loop between ROS and NLRP3 inflammasome. The precise mechanism of how ROS affects NLRP3 inflammasome activation still need to be addressed. This review will summarize the current knowledge on the molecular mechanisms underlying the activation of NLRP3 inflammasome with particular emphasis on the intricate balance of feedback loop between ROS and inflammasome activation. Understanding that this relationship is loop rather than traditionally understood linear mechanism will enable to fine-tune inflammasome activation under varied pathological settings. 36, 784-796.